2017
DOI: 10.1097/j.pain.0000000000000936
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptor interleukin 10 receptor 1 is critical for muscle analgesia induced by repeated bouts of eccentric exercise in the rat

Abstract: Delayed-onset muscle soreness is typically observed after strenuous or unaccustomed eccentric exercise. Soon after recovery, blunted muscle soreness is observed on repeated eccentric exercise, a phenomenon known as repeated bout effect (RBE). Although regular physical activity decreases muscle hyperalgesia, likely because of increased production of the anti-inflammatory cytokine interleukin-10 (IL-10) in the skeletal muscle, whether IL-10 also contributes to the antinociceptive effect of RBE is unknown. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 51 publications
2
22
1
3
Order By: Relevance
“…Results were analyzed using computer-assisted densitometry with levels of TLR4 immunoreactivity normalized with respect to the ␤-actin control levels in the same sample. The percentage decrease in TLR4 expression was calculated as follows: [normalized density for AS/normalized density for MM ϫ 100] Ϫ 100 (Summer et al, 2008;Alvarez et al, 2017).…”
Section: Sds-page and Western Blottingmentioning
confidence: 99%
“…Results were analyzed using computer-assisted densitometry with levels of TLR4 immunoreactivity normalized with respect to the ␤-actin control levels in the same sample. The percentage decrease in TLR4 expression was calculated as follows: [normalized density for AS/normalized density for MM ϫ 100] Ϫ 100 (Summer et al, 2008;Alvarez et al, 2017).…”
Section: Sds-page and Western Blottingmentioning
confidence: 99%
“…Changes in protein expression of IL-33 in skeletal muscle and IL-33R/ST2 in L4-L5 DRGs were evaluated by Western blot as previously described. 1,2,6 Briefly, rats were killed by exsanguination, while under deep isoflurane anesthesia, 24 hours after vibration or last i.t. ODN injection.…”
Section: Tissue Harvesting and Western Blot Analysismentioning
confidence: 99%
“…12,24,35,37 Although the role of IL-33 in muscle pain is unknown, evidence indicates that nociceptors dynamically sense local levels of cytokines after muscle injury, modifying their responses to mechanical stimulation, in a time-dependent manner. 1,2,6,8 Therefore, by sensing local IL-33 levels, nociceptors could also provide important inputs for adaptive behaviors after muscle injury. Such a functional arrangement is possible, since the canonical receptor for IL-33, IL-33R (also known as suppression of tumorigenicity 2 [ST2] or interleukin 1 receptor-like 1 [IL1RL1]), and its co-partner for IL-33 signaling, the interleukin 1 receptor accessory protein (IL1RAcP, also known as IL1RAP), are expressed in human and mouse DRG neurons.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that physical resilience, the intrinsic capacity to recover from tissue injury, exhibits a cytokine signature, which is detected by muscle nociceptors. 2 Disruption of a nociceptor's capacity to detect this signature prevents the recovery of baseline nociceptive threshold. 2 The fact that nociceptors also respond to the sympathoadrenal mediator epinephrine 12,35 suggests that stress can also modulate the function of nociceptors as sensors of the physical resilience status.…”
Section: Introductionmentioning
confidence: 99%